Strategies for Balancing Cost Management and Employee Retention in Mexico’s Electronics Industry Amid Minimum Wage Increases - Ricardo J. Pacheco Vargas (Law and Economy, 2025)
The increase in Mexico’s minimum wage has created significant challenges for the electronics industry, requiring companies to balance cost management with employee retention while maintaining competitiveness. This paper explores how multinational and domestic electronics manufacturers in Mexico are adapting to rising labor costs through lean manufacturing, automation, workforce development, and supply chain optimization. By analyzing industry trends, case studies, and global comparisons, the study identifies the most effective cost-saving and retention strategies, highlighting the differences between large multinational corporations and mid-sized domestic firms. The findings suggest that while automation and supply chain adjustments help mitigate rising costs, workforce-focused strategies such as upskilling programs, performance-based incentives, and career growth opportunities are crucial for long-term retention. The study also examines the role of government policies in supporting wage adjustments, emphasizing the need for training initiatives, tax incentives for automation, and labor market flexibility. Ultimately, the research concludes that companies that integrate technological advancements with employee engagement strategies will be better positioned to maintain profitability and workforce stability in a changing economic landscape.